A novel electroluminescent device based on a reduced graphene oxide wrapped phosphor (ZnS:Cu, Al) and hexagonal-boron nitride for high-performance luminescence. Issue 15 (6th April 2017) - Gupta, Bipin Kumar; Singh, Satbir; Kedawat, Garima; Kanika,; Kumar, Pawan; Gangwar, Amit Kumar; Narayanan, Tharangattu N.; Marti, Angel A.; Vajtai, Robert; Ajayan, P. M.
Abstract : An rGO wrapped ZnS:Cu, Al as an emitting layer and exfoliated h-BN as the dielectric layer for next generation EL devices. Abstract : Reduced graphene oxide (rGO) has recently emerged as a very promising family of exotic carbon material with augmented performance in electronic and optoelectronic devices. Herein, we report an efficient and novel inorganic electroluminescent device geometry, where a new phosphor composite, reduced graphene oxide wrapped ZnS:Cu, Al, acts as an active emitting layer and an exfoliated hexagonal boron nitride (h-BN) as a dielectric layer. The roles of rGO in the active layer as a conductive support and local electric field enhancing agent are attributed to its wrinkles being unraveled compared with other carbon exotic nano-forms such as carbon nanotubes, graphite, charcoal and activated carbon, which significantly improves the brightness of the device (∼50 cd m −2 for 0.50 wt % rGO/ZnS:Cu, Al at 10 kHz and 110 V with an external quantum efficiency of ∼6.3% ± 0.1% and current efficiency of ∼0.81 ± 0.09 cd A −1 ). This new and facile strategy to construct the luminescent devices could be a paradigm shift towards cost effective, highly stable in air (for several days) and energy efficient next generation display devices.